Digitalization and Banking Crisis: A Nonlinear Relationship? - Mohamed Sami Ben Ali (14152038) (2022)
This study assesses the impact that ICT can have on the occurrence of banking crisis for a sample of 113 countries over the period 1996–2017 while considering the interfering role of corruption and the potential existence of a nonlinear relationship for the ICT-banking crisis nexus. We consider countries with varying income levels to check for the stability of the relationship. Our estimation results show that more highly ICT endowed countries can improve the resilience of the banking system. The study provides evidence that ICTs do not produce the same effect regardless of a country’s level of income. Estimation outcomes show the existence of a threshold effect driving the ICT-banking stability nexus. More results show that Information and communication technologies can improve the stability of the banking system only when corruption is relatively low. However, when corruption is endemic, ICT endowment is useless for the stability of the banking system. Other Information Published in: Journal of Quantitative Economics License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1007/s40953-022-00292-0